Strategi Guru: Berpikir Kritis dalam IPS Berbasis Deep Learning - Suyanti, Suyanti; Vivi Rulviana; Eka Nofri Ariyanto; Tasya, Tasya (Politeknik Kampar, 2025)
This study intends to comprehensively describe social studies learning with a Deep Learning approach, as well as to know its role as an effort to strengthen students' thinking skills. This research uses a descriptive qualitative method by collecting data through observation, teacher and student interviews, and documentation review. The research subjects involved one social studies teacher as a key informant, as well as eight social studies grade IV students at Maospati Elementary School in Magetan who were selected purposively based on active involvement in learning and adequate communication skills. Data analysis uses data reduction, data presentation, and triangulation techniques to ensure the validity of research findings. The results of the study show that learning strategies emphasize discussion, problem solving, and reflection which significantly improve students' critical thinking skills. Obstacles experienced by teachers in learning include limited time, variations in students' abilities, and lack of relevant supporting learning resources. However, the application of the Deep Learning approach still shows its effectiveness in increasing concept understanding, learning independence, and student activity during the learning process in the classroom.